Kelas Ibu Hamil sebagai Media Komunikasi Tenaga Kesehatan dan Ibu Hamil - Aisyah, Farah Aulia; Prastyanti, Shinta; Ganjar Runtiko, Agus (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2023)
The Maternal Mortality Ratio (MMR) in Banyumas Regency in 2021 was 44 maternal deaths, equivalent to a rate of 181.09 per 100,000 live births. The MMR target set in the National Medium-Term Development Plan (RPJMN) for the period 2019-2024 is 70 per 100,000 live births, indicating that the target has not been achieved in Banyumas Regency. Based on the data on Maternal Mortality Ratio in Banyumas Regency, one of the interventions needed is the implementation of antenatal classes as a communication medium between pregnant women and healthcare providers. Antenatal classes provide pregnant women with increased knowledge about pregnancy, while healthcare providers gain a better understanding of the health conditions of each pregnant woman. The aim of this study is to examine how antenatal classes serve as a communication medium between pregnant women and healthcare providers. The study employed a qualitative descriptive method with purposive sampling to select three healthcare providers from Banyumas Primary Health Centers and five participants from antenatal classes as informants. The research focused on the Antenatal Class Program in Sudagaran Village. Data were collected through interviews, observations, and documentation, and analyzed using the interactive model of Miles and Huberman. The results indicate that antenatal classes have been conducted in Sudagaran Village since 2012. As a communication medium, antenatal classes in Sudagaran Village serve as a platform for information dissemination, discussions, as well as education and value instruction for pregnant women in the community.